TO‘QIMACHILIK SANOATI XOMASHYOSIDAN SAMARALI FOYDALANISH ORQALI YANGI TARKIBLI PISHITILGAN IPLAR ISHLAB CHIQARISHNING AYRIM YO‘LLARI (Multidisciplinary Journal of Science and Technology, 2025)
The scientific article presents variants of compositions of blended fibers for new technologies of yarn production from existing textile raw materials, results and analysis of laboratory tests. Conclusions are made on the criteria for the optimality of these variants.